Sludge anaerobic digestion methane production method based on direct interspecific electron transfer
By using SC/FeS composite materials as conductive materials in the anaerobic digestion system, the problem of low DIET efficiency is solved, methane yield and system stability are significantly improved, and a more efficient anaerobic digestion effect is achieved.
Patent Information
- Application Number
- CN202411378517.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The current direct interspecies electron transfer (DIET) has a small efficiency and proportion in anaerobic digestion, and the electrically active bacteria's conductive flagella and cytochrome C are limited in the anaerobic environment, resulting in imbalance in methanation and yield. Low.
Using SC/FeS composite material as conductive material, carbon material with honeycomb structure is prepared by gradient heating pyrolysis technology, and ferrous sulfide (FeS) particles are loaded on its surface to form SC/FeS composite material and add it to sludge. Anaerobic digestion to increase methane production.
The methane production of the microbial anaerobic digestive system has been significantly improved, with a maximum yield of 3.75 times, enhancing the stability and impact load resistance of the system, and improving the acid imbalance problem.
Smart Images

Figure CN119219286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment and resource utilization, in particular to the technical field of microbial anaerobic fermentation, and specifically to a method for producing methane by anaerobic digestion of sludge based on direct interspecies electron transfer. Background Art
[0002] Anaerobic digestion mainly involves the degradation of organic matter by anaerobic bacteria under anaerobic conditions, and the conversion of organic matter into carbon dioxide and methane. In this process, harmful substances in sludge are decomposed, the total amount of sludge is reduced, and energy gases such as hydrogen and methane are obtained, which realizes the resource utilization of sludge while achieving sludge stabilization. Most organic matter exists in sludge flocs, so appropriate pretreatment is required to promote the release of intracellular organic matter and accelerate the subsequent acid production and methanogenesis. However, there are significant differences between the acid production stage and the methanogenesis stage in terms of microbial ecology, metabolic rate, and environmental adaptability. This makes it very easy for changes in operating conditions, such as temperature, organic load, pH, etc., to destroy the metabolic balance between acid production and methanogenesis, resulting in an imbalance and stagnation of methanogenesis. Therefore, maintaining the metabolic balance between acid production and methanogenesis is the key to strengthening anaerobic digestion. Acidogenic bacteria and methanogenic bacteria use H2 and formic acid as electron carriers to achieve effective electron exchange between each other, thereby realizing the conversion of organic matter into methane, which is indirect interspecies electron transfer (MIET). MIET is susceptible to fluctuations in hydrogen partial pressure, resulting in acid imbalance.
[0003] Studies in recent years have confirmed that in the mutualistic system composed of electroactive bacteria and methanogens, the former can transfer the electrons generated by intracellular metabolism to methanogens through their conductive flagella and cytochrome C to achieve methane production, and this electron transfer process that does not require the participation of external electron carriers is called direct interspecies electron transfer (DIET). At present, DIET is widely used in the anaerobic digestion treatment of high-concentration organic wastewaters such as brewery wastewater and aquaculture wastewater. Compared with MIET, DIET does not involve the generation, diffusion and utilization of electron carriers, improves the acid imbalance problem, and therefore has become a hot spot and frontier of research. However, due to the limited accessibility of the conductive flagella and cytochrome C of electroactive bacteria in anaerobic environments, and the relatively limited construction process of DIET, its actual application efficiency and proportion in anaerobic digestion are relatively small.
[0004] Some people have studied the introduction of conductive materials into DIET to solve the problem of limited accessibility and enhance the efficiency of DIET. At present, most conductive materials use metallic iron. For example, CN112250271A discloses a method for promoting the anaerobic digestion and methane production of excess sludge by combining metal conductive materials with sludge pretreatment, which mixes the metal mesh and sludge and puts them into an anaerobic digestion reactor for anaerobic digestion and methane production. In the anaerobic digestion system, Fe ions provide electrons and reduce the redox potential, promoting methane yield. However, Fe ions are prone to agglomeration and have poor stability, thereby inhibiting electron transfer and reaction activity, limiting application. Summary of the invention
[0005] The object of the present invention is to provide a method for producing methanogen by anaerobic digestion of sludge based on direct interspecies electron transfer, so as to improve the efficiency of the microbial anaerobic digestion system.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for producing methane by anaerobic digestion of sludge based on direct interspecies electron transfer, wherein a conductive material is added to the sludge, and an anaerobic digestion reaction is carried out under stirring; the conductive material is a SC / FeS composite material. In the present application, the addition of the conductive material can increase the methane production by 1.2-3.75 times.
[0008] In a further embodiment, the weight of the SC / FeS composite material added is 0.3-0.8 g / L of the sludge mixed liquid volume.
[0009] In a further embodiment, the stirring conditions are: 30-40° C., 100-150 rpm.
[0010] In a further embodiment, the preparation method of the SC / FeS composite material comprises the following steps:
[0011] (1) pyrolyzing the dried sodium citrate at a higher temperature to obtain a carbon material having a honeycomb structure;
[0012] (2) adding the ferrous chloride solution to the carbon material prepared in step (1), stirring and ultrasonically dispersing; then centrifuging the mixed solution to obtain a pyrolyzed carbon solid adsorbed with iron ions;
[0013] (3) adding the sodium sulfide solution to the pyrolyzed carbon solid in step (2) and mixing them;
[0014] (4) The mixture of step (3) is aerated with nitrogen and then sealed and aged, and then washed with oxygen-free water and freeze-dried to obtain a SC / FeS composite material.
[0015] In a further embodiment, in step (1), the temperature rise pyrolysis is performed by heating to 600°C at a heating rate of 5°C / min and pyrolyzing for 2-4h; and then cooling to room temperature at a cooling rate of 5°C / min.
[0016] In a further embodiment, in step (1), the carbon material is first washed with a hydrochloric acid solution having a concentration of 0.8-1.2 mol / L, and then washed with deionized water until neutral, and then dried.
[0017] In a further embodiment, the ferrous chloride solution is formed by dissolving ferrous chloride tetrahydrate in deionized water, and the sodium sulfide solution is formed by dissolving sodium sulfide nonahydrate in deionized water; the molar ratio of ferrous chloride tetrahydrate to sodium sulfide nonahydrate is 1-2:2, and the mass ratio of sodium sulfide nonahydrate to pyrolytic carbon is 16-24:1.
[0018] In a further embodiment, in step (2), the ultrasonic dispersion is performed for 2-4 hours to ensure that the divalent iron ions are completely adsorbed on the surface of the pyrolytic carbon.
[0019] In a further embodiment, in step (4), the nitrogen aeration time is 30-60 minutes, and after sealing, the mixture is placed in a shaker for even shaking and aged for at least 24 hours. The solid material is then washed with oxygen-free water and centrifuged or filtered to obtain a solid material, which is then placed in a freeze dryer for freeze drying to obtain a SC / FeS composite material.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] The present invention adds SC / FeS composite materials as conductive materials to sludge, which can improve the efficiency of microbial anaerobic digestion, realize resource utilization of wastewater treatment, and increase methane production by 1.2-3.75 times.
[0022] The carbon material in the SC / FeS composite material has abundant specific surface area and excellent chemical stability, which is conducive to the attachment and growth of microorganisms; while ferrous sulfide (FeS) has high electron mobility and excellent biocompatibility, and can effectively collect and transfer electrons. Therefore, the present application combines the two to give full play to the advantages of both and improve the comprehensive performance of the composite material. Therefore, using the SC / FeS composite material as an anaerobic digestion conductive material can enhance DIET and promote the efficiency of the anaerobic digestion system.
[0023] The present invention utilizes gradient temperature rise pyrolysis technology to convert sodium citrate into a carbon material (SC) with a honeycomb structure, and uses it to adsorb secondary iron ions to synthesize a SC / FeS composite material. Adding it into a sewage anaerobic treatment system can significantly increase the methane production of the microbial anaerobic digestion system, which is mainly due to the good biocompatibility, rapid mass transfer capacity and electron transfer capacity of SC; secondly, on this basis, ferrous sulfide FeS particles with good conductivity are loaded on the surface of SC, so that the maximum methane production rate of the microbial anaerobic digestion system is doubled compared with the addition of a single SC, which is mainly due to the fact that the loading of FeS significantly enhances the electrical conductivity of SC, and the synergistic effect between SC and FeS effectively promotes the progress of the microbial anaerobic digestion process. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 are scanning electron microscope images of materials, wherein a is a scanning electron microscope image of SC prepared in step (1) of Example 1, b is a scanning electron microscope image of single FeS, and c and d are scanning electron microscope images of SC / FeS composite materials prepared in Example 1 at different sizes;
[0025] Figure 2 Fourier transform infrared spectra (FTIR) of SC, FeS and the SC / FeS composite material prepared in Example 1;
[0026] Figure 3 X-ray photoelectron spectroscopy (XPS) of SC, FeS and the SC / FeS composite material prepared in Example 1;
[0027] Figure 4 is a high-resolution XPS spectrum of the elements, wherein a1 is a high-resolution XPS spectrum of the C element in the SC material, and a2 is a high-resolution XPS spectrum of the C element in the SC / FeS composite material prepared in Example 1,
[0028] b1 is the high-resolution XPS spectrum of the S element in FeS material.
[0029] b2 is the high-resolution XPS spectrum of the S element in the SC / FeS composite material prepared in Example 1,
[0030] c1 is the high-resolution XPS spectrum of Fe element in FeS material.
[0031] c2 is the high-resolution XPS spectrum of the Fe element in the SC / FeS composite material prepared in Example 1;
[0032] Figure 5 Electrochemical impedance spectroscopy (EIS) of SC, FeS and the SC / FeS composite material prepared in Example 1;
[0033] Figure 6 It is a line chart showing the cumulative methane production changes of group B and the control group to which the SC / FeS composite material was added in Example 2;
[0034] Figure 7 This is a bar chart showing changes in methane production in the anaerobic digestion system with different added materials after experiencing shock load in Example 3 of the present invention. DETAILED DESCRIPTION
[0035] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention; the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] A method for preparing a SC / FeS composite material comprises the following steps:
[0038] (1) drying the sodium citrate particles in an oven at 120° C. for 12 h; then, heating the dried sodium citrate in a tube furnace to 600° C. at a heating rate of 5° C. / min and pyrolyzing for 2 h; then, cooling the temperature to room temperature at a cooling rate of 5° C. / min;
[0039] The product obtained after pyrolysis was first washed with 200 mL of 1 mol / L hydrochloric acid solution, then washed with deionized water until neutral, and finally dried in an oven at 60°C for 24 h to obtain a honeycomb-structured carbon material (SC) with a large specific surface area;
[0040] (2) 3.43 g (0.017 mol) of ferrous chloride tetrahydrate was dissolved in deionized water, and then added to 300 mg of the carbon material prepared in step (1), stirred and ultrasonically dispersed for 2 h to fully load the SC surface with divalent iron ions; then the mixed solution was centrifuged and filtered, and excess ferrous solution was removed to prevent the divalent iron ions adsorbed on the SC surface from being oxidized by air; and a pyrolytic carbon solid adsorbed with iron ions was obtained;
[0041] (3) Weigh 4.76 g (0.02 mol) of sodium sulfide nonahydrate, dissolve it in 36 mL of deionized water, and add it to the pyrolyzed carbon solid prepared in step (2) and mix them;
[0042] (4) The mixture of step (3) was exposed to nitrogen for 30 minutes, and then sealed and placed in a shaker for even shaking, aged for at least 24 hours, and then washed with oxygen-free water for 3 times, centrifuged, filtered, and separated to obtain a solid material, and finally placed in a freeze dryer for freeze drying to obtain a SC / FeS composite material.
[0043] like Figure 1 a is a scanning electron microscope image of the SC prepared in step (1) of Example 1, b is a scanning electron microscope image of a single FeS, and c and d are scanning electron microscope images of the SC / FeS composite material prepared in Example 1 at different sizes, indicating that the prepared SC / FeS composite material has a higher porosity and a larger specific surface area.
[0044] like Figure 2 The Fourier transform infrared spectra (FTIR) of SC, FeS and the SC / FeS composite material prepared in Example 1 are shown. -1 and 672cm -1 The vibration peaks of 1160cm-1 correspond to C=O and C-H bonds, which may be associated with aromatic compounds through functional groups such as ketones, aldehydes or carboxylic acids. -1 and 1110cm -1 The absorption peaks of SC / FeS correspond to CO (or CC) and CO bonds, respectively, which may exist in the form of quinones and hydroquinones. According to the theory that there are reversible transformations between functional species, phenolic hydroxyl and quinone (CO) can undergo electron-mediated transformation. Therefore, it is speculated that the SC / FeS composite material may have the function of an electron shuttle and promote the occurrence of direct interspecies electron transfer (DIET).
[0045] like Figure 3 , Figure 4 The X-ray photoelectron spectroscopy (XPS) spectra of SC, FeS and the SC / FeS composite material prepared in Example 1 and the high-resolution XPS spectra of each element are shown, the surface functional groups of the SC / FeS composite material are further determined, and it is proved that the SC / FeS composite material is successfully prepared.
[0046] like Figure 5 Electrochemical impedance spectroscopy (EIS) of SC, FeS, and the SC / FeS composite prepared in Example 1 is shown. The results show that the SC / FeS composite has significantly better conductivity, which helps to enhance the efficiency of the direct electrochemical reaction (DIET) process.
[0047] Embodiment 2:
[0048] Anaerobic digestion applications:
[0049] In this example, the SC / FeS composite material prepared in Example 1 was applied to an anaerobic granular sludge microbial anaerobic digestion methanogenesis system.
[0050] In the experiment, a 500mL anaerobic serum bottle was used as the anaerobic bioreactor, and the substrate was artificially simulated wastewater with a COD concentration of 4000mg / L; the anaerobic sludge was taken from the COFCO sewage treatment station in Bengbu City, Anhui Province, and its moisture content was 86.29%.
[0051] The test was divided into two groups, A and B, with three parallel samples in each group. 1.25 g of the above-mentioned anaerobic sludge and 250 mL of wastewater were added to each parallel sample. After stirring and mixing, the sludge concentration was 5 g / L.
[0052] Group A: The control group, in which no material was added;
[0053] Group B: The SC / FeS composite material prepared in Example 1 was added, and the concentration of the SC / FeS composite material in the mixed solution was 0.5 g / L after stirring.
[0054] All reactions were carried out in a shaking incubator at a constant temperature of 35°C and 120 rpm. Dissolved oxygen in the wastewater was removed by nitrogen stripping to maintain an anaerobic environment, and the bottle was sealed at the mouth. The biogas produced during the reaction was collected by a syringe, and the relative content of methane (CH4) and carbon dioxide (CO2) in the biogas was analyzed by gas chromatography, and the volume of air at the top of the reactor was recorded.
[0055] During the reaction, 5 mL of water sample was taken from the top of the reactor by syringe at the same time point, and then the water sample was squeezed and filtered, processed through a 0.45 μm filter membrane, and the COD in the treated wastewater was measured and the data was recorded.
[0056] like Figure 6 The effect of adding SC / FeS composite material to group B on the methane production in the microbial anaerobic digestion system at an initial COD concentration of 4000 mg / L was demonstrated. The addition of SC / FeS composite material significantly increased the methane production in the microbial anaerobic digestion system, which was 1.5 times higher than that of the control group (group A) without adding the material. The Gompertz model was used to fit the data (P = P0exp(-exp[Rmaxe(t0-t) / p0+1])), which further confirmed that in the start-up stage of anaerobic digestion, the addition of SC / FeS composite material increased the maximum methane yield by 3.75 times compared with the control group. Therefore, it is feasible to use SC / FeS composite material to strengthen the microbial anaerobic digestion system to increase methane production.
[0057] Example 3
[0058] Based on Example 1 and Example 2, experiments were conducted to evaluate the strengthening effect of the SC / FeS composite material on the recovery of shock load (starvation state) in the anaerobic digestion system.
[0059] The experiment was conducted on the basis of Example 2, with two more groups added. Other conditions remained unchanged, and the four groups were divided into A, B, C and D. Three parallel samples were set in each group. 1.25 g of the above anaerobic sludge and 250 mL of wastewater were added to each parallel sample. After stirring and mixing, the sludge concentration was 5 g / L.
[0060] Specifically:
[0061] Group A: The control group, in which no material was added;
[0062] Group B: a control group, to which the single SC material prepared in Example 1 was added, and the concentration of the SC material in the mixed solution was 0.5 g / L after stirring;
[0063] Group C: The control group, in which FeS material was added alone and stirred to make the concentration of FeS material in the mixed solution 0.5 g / L;
[0064] Group D: The SC / FeS composite material prepared in Example 1 was added, and the concentration of the SC / FeS composite material in the mixed solution was 0.5 g / L after stirring.
[0065] After 5 mL of water sample was drawn from the top of the reactor using a syringe at each time point, 5 mL of simulated artificial wastewater with a COD of 3000 mg / L was added for a 1-month acclimatization treatment, followed by a 15-day shock load treatment (starvation treatment).
[0066] After this stage, high concentration of artificial synthetic wastewater was added to ensure that the COD concentration of the solution in the anaerobic bioreactor was maintained at 3000 mg / L. The biogas produced during the reaction was collected by a syringe, and the relative contents of methane (CH4) and carbon dioxide (CO2) in the biogas were analyzed by gas chromatography. The total gas production of the reactor was monitored by the drainage gas collection method.
[0067] like Figure 7 As shown, it shows the effect of restoring exogenous material addition on methane production in the anaerobic digestion system after experiencing shock load (starvation). On the first day of reaction, the methane production of the group adding SC / FeS composite material increased by 8.4% compared with the control group; on the sixth day of reaction, with the recovery of the anaerobic digestion system, the methane production of the SC / FeS composite material group increased by 17.47% compared with the control group, and the cumulative methane production was also 3.8% higher than that of the control group. These results show that the addition of SC / FeS composite material significantly enhances the shock load resistance of the anaerobic reactor and is conducive to the recovery of the damaged microbial anaerobic digestion system.
[0068] Embodiment 4:
[0069] A method for preparing a SC / FeS composite material comprises the following steps:
[0070] (1) drying the sodium citrate particles in an oven at 100° C. for 15 h; then, heating the dried sodium citrate in a tube furnace to 600° C. at a heating rate of 5° C. / min and pyrolyzing for 4 h; then, cooling the mixture to room temperature at a cooling rate of 5° C. / min;
[0071] The product obtained after pyrolysis was first washed with 200 mL of 1.2 mol / L hydrochloric acid solution, then washed with deionized water until neutral, and finally dried in an oven at 80°C for 20 h to obtain a honeycomb-structured carbon material (SC) with a large specific surface area;
[0072] (2) 3.94 g (0.02 mol) of ferrous chloride tetrahydrate was dissolved in deionized water, and then added to 300 mg of the carbon material prepared in step (1), stirred and ultrasonically dispersed for 4 h to fully load the SC surface with divalent iron ions; then the mixed solution was centrifuged and filtered, and excess ferrous solution was removed to prevent the divalent iron ions adsorbed on the SC surface from being oxidized by air; and a pyrolytic carbon solid with adsorbed iron ions was obtained;
[0073] (3) weighing 7.2 g (0.03 mol) of sodium sulfide nonahydrate, dissolving it in deionized water, and adding it to the pyrolyzed carbon solid prepared in step (2) and mixing them;
[0074] (4) The mixture of step (3) was exposed to nitrogen for 60 minutes, then sealed and placed in a shaker for uniform shaking, aged for 28 hours, washed with oxygen-free water for 3 times, centrifuged, filtered, and separated to obtain a solid material, and finally placed in a freeze dryer for freeze drying to obtain a SC / FeS composite material.
[0075] Embodiment 5:
[0076] The same as Example 2, except that the SC / FeS composite material prepared in Example 4 was added, and the concentration of the SC / FeS composite material in the mixed solution was 0.8 g / L after stirring at 40° C. and 100 rpm.
[0077] The results showed that the addition of SC / FeS composite materials significantly increased the methane production in the microbial anaerobic digestion system, which was 3 times higher than that of the control group (Group A) without the addition of materials.
[0078] Embodiment 6:
[0079] The same as Example 2, except that the SC / FeS composite material prepared in Example 4 was added, and the concentration of the SC / FeS composite material in the mixed solution was 0.3 g / L after stirring at 30° C. and 150 rpm.
[0080] The results showed that the addition of SC / FeS composite materials significantly increased the methane production in the microbial anaerobic digestion system, which was 1.2 times higher than that of the control group (Group A) without the addition of materials.
[0081] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for producing methanogen by anaerobic digestion of sludge based on direct interspecies electron transfer, characterized in that: A conductive material is added to the sludge, and an anaerobic digestion reaction is carried out under stirring; the conductive material is a SC / FeS composite material.
2. The method for producing methanogen by anaerobic digestion of sludge according to claim 1, characterized in that: The weight of the SC / FeS composite material added accounts for 0.3-0.8 g / L of the volume of the sludge mixed liquid.
3. The method for producing methanogen by anaerobic digestion of sludge according to claim 1, characterized in that: The stirring conditions are 30-40°C and 100-150rpm.
4. The method for producing methanogen by anaerobic digestion of sludge according to claim 1, characterized in that: The preparation method of the SC / FeS composite material comprises the following steps: (1) pyrolyzing the dried sodium citrate at a higher temperature to obtain a carbon material having a honeycomb structure; (2) adding the ferrous chloride solution to the carbon material prepared in step (1), stirring and ultrasonically dispersing; then centrifuging the mixed solution to obtain a pyrolyzed carbon solid adsorbed with iron ions; (3) adding the sodium sulfide solution to the pyrolyzed carbon solid in step (2) and mixing them; (4) The mixture of step (3) is aerated with nitrogen and then sealed and aged, and then washed with oxygen-free water and freeze-dried to obtain a SC / FeS composite material.
5. The method for producing methanogen by anaerobic digestion of sludge according to claim 4, characterized in that: In step (1), the temperature rise pyrolysis is to heat to 600°C at a heating rate of 5°C / min, pyrolyze for 2-4h; and then cool to room temperature at a cooling rate of 5°C / min.
6. The method for producing methanogen by anaerobic digestion of sludge according to claim 4, characterized in that: In step (1), the carbon material is first washed with a hydrochloric acid solution having a concentration of 0.8-1.2 mol / L to clean the pyrolysis product, then washed with deionized water until neutral, and then dried.
7. The method for producing methanogen by anaerobic digestion of sludge according to claim 4, characterized in that: The ferrous chloride solution is formed by dissolving ferrous chloride tetrahydrate in deionized water, and the sodium sulfide solution is formed by dissolving sodium sulfide nonahydrate in deionized water; the molar ratio of ferrous chloride tetrahydrate to sodium sulfide nonahydrate is 1-2:2, and the mass ratio of sodium sulfide nonahydrate to pyrolytic carbon is 16-24:
1.
8. The method for producing methanogen by anaerobic digestion of sludge according to claim 4, characterized in that: In step (2), the ultrasonic dispersion is performed for 2-4 hours.
9. The method for producing methanogen by anaerobic digestion of sludge according to claim 4, characterized in that: In step (4), the nitrogen aeration time is 30-60 minutes. After sealing, the mixture is placed in a shaker and shaken evenly for aging for at least 24 hours.
Citation Information
Patent Citations
Organic pollutant degradation method based on biological nano hybrid system
CN112960781A
Conductive material for strengthening anaerobic digestion and preparation method thereof
CN115747261A
Method for producing methane by enhancing anaerobic fermentation of kitchen waste based on biologically self-synthesized iron sulfide
CN118480592A
Accelerated start-up of anaerobic reactors based on conductive nanomaterials
JP7046298B1
Cited By
Magnetic iron-carbon composite material and application thereof in increasing methane yield in anaerobic digestion system
CN121554099A
